Trends and Drivers of Poverty Reduction in Nepal : A Historical Perspective - Uematsu, Hiroki; Shidiq, Akhmad Rizal; Tiwari, Sailesh (World Bank, Washington, DC, 2016)
Nepal made remarkable progress in poverty reduction between 1995 and 2010, a period coinciding with a decade-long violent conflict followed by tumultuous post-conflict recovery. Although improving agricultural productivity was long regarded as instrumental to lifting the living conditions of Nepal's impoverished rural areas, a bulk of the observed poverty reduction has come as a result of exogenous improvements in economic opportunities for poor Nepalis outside Nepal's borders. About 50 percent of the poverty reduction witnessed between 1995 and 2010 was associated with growth in labor incomes, particularly in nonagricultural activities. Private remittance receipts account for a little over a quarter of the total poverty reduction seen in Nepal. This is consistent with increased nonfarm diversification of rural households as well as the increase in nonfarm wages over the period. Household demographic changes, brought about by a sharp decline in fertility rates and the changing dependency structure as a result of migration, have also played an important role.